A fuzzy disturbance observer based control approach for a novel 1-DOF micropositioning mechanism. (February 2020) - Al-Jodah, Ammar; Shirinzadeh, Bijan; Ghafarian, Mohammadali; Kumar Das, Tilok; Tian, Yanling; Zhang, Dawei
Highlights: Novel compact, large range 1-DOF micro manipulation mechanism is proposed. The proposed design is extendable to multi-DOF mechanism designs. Fuzzy disturbance observer based sliding mode controller is proposed. High positioning resolution of around 40 nano-meter is achived. Superior tracking performance is achieved with the proposed controller. Abstract: This paper presents the design, analysis, and control of a novel compact, large range 1-DOF micro manipulation mechanism. Leaf flexures were incorporated into a modular multilayer design configuration to achieve large range motion with a high natural frequency. The modular design of the proposed mechanism makes it usable as a building block to construct higher DOF-mechanisms. Computational analysis was conducted to verify the static and dynamic responses of the proposed mechanism and to ensure low flexures stress, high natural frequency, and large workspace. The mathematical model was developed to establish the derivation of a robust observer-based Sliding Mode (SM) controller. To improve the precision of tracking performance, the SM controller was augmented with adaptive Fuzzy Disturbance Observer (SM-FDO). Another robust control technique (H∞ ) was implemented in this work to characterize and compare the performance of SM-FDO. The mechanism was fabricated using 3D printing technology and a Voice Coil Motor (VCM) was used to deliver the actuation for its capability to provide large displacements. Experiments were performed to verify the computational modeling of the proposed mechanism and to evaluate the performance of the developed controllers. Several experimental results showed that the adaptive nature of SM-FDO allowed this controller to have superior robustness and tracking performance over the other implemented robust controller.